The Mindfulness Map: A Practical Classification Framework of Mindfulness Practices, Associated Intentions, and Experiential Understandings - Levit-Binnun, Nava; Arbel, Keren; Dorjee, Dusana (Frontiers in Psychology, 2021)
When considering the numerous mindfulness-based and mindfulness-informed programs that have flourished in the past decades it is not always clear that they all refer to the same “mindfulness. ” To facilitate more clarity and precision in describing, researching and teaching mindfulness in the secular settings, we propose a classification framework of mindfulness practices, intentions behind them and the experiential understandings the practices may aim to develop. Accordingly, the proposed framework, called the Mindfulness Map, has two axes. The first axis outlines mindfulness practices (and associated instructions) classified into four groups (MGs), e.g. the MG1 focuses on cultivating attention to the present moment somatic and sensory experience while the MG4 focuses on cultivating the ability to recognize and deconstruct perceptual, cognitive and emotional experiences and biases. The second axis outlines possible intentions (INTs) to cultivate particular experiential understanding (EU) via teaching and practicing the MGs, e.g., the INT1 designates the intention to gain EU of how our relationship to experience contributes to wellbeing, the INT2 refers to the intention to gain EU of the changing nature of body, mind and external phenomenon. We suggest that the same MG can lead to different EUs outcomes based on the specific INTs applied in their teaching or practice. The range of INTs and EUs included here is not exhaustive, there are further types the Map could be expanded toward. Aside from encouraging more fine-grained distinctions of mindfulness practices, the proposed Map aims to open discussions about interactions between MGs, INTs, EUs and practice outcomes. The Map may facilitate more nuanced and precise approaches to researching the range of outcomes cultivated by mindfulness practices, help bridge contradictory findings, and catalyze further debate and research into ethical aspects of mindfulness. The Map also highlights the need for further teaching development and research on longer-term trajectories of mindfulness practice. While the proposed Mindfulness Map organises the mindfulness practice territory along two axes, it is aimed as a starting point for further discussion and can be further revised and/or expanded by other axes.